Case Report: Extreme resistance to subcutaneous insulin in a cirrhotic patient with new-onset diabetes that resolved after transplantation - Tunez, Kim; Ringwald-de Meyer, Sara; Barigou, Mohammed; Kosinski, Christophe (Frontiers in Endocrinology, 2025)
Although an increase in insulin resistance is frequently associated with liver cirrhosis, a condition sometimes referred to as hepatogenic diabetes (HD), the pathophysiology is still poorly understood. Moreover, the management of patients with HD, both diagnostically and therapeutically, is complex. In this article, we present the case of a cirrhotic patient, initially not known to have diabetes or prediabetes, who developed fulminant diabetes overnight, with massive resistance to subcutaneous insulin treatment. Management during hospitalization was extremely complicated, leading to significant staggering of the insulin doses until the liver transplant, which allowed complete normalization of the glycemic profile.